The Pfeiffer book of successful team-building tools : (Pfeiffer, 2008)
Year after year, consultants, trainers, and human resource professionals have come to rely on The Pfeiffer Annuals to provide them with the most current and quality tools on a wide variety of topics. In this book, editor Elaine Biech and contributors to the Annuals have honed in on the important theme of team building to create the first topic-specific book in The Pfeiffer Annuals series. The Pfeiffer Book of Successful Team-Building Tools, 2nd Edition, includes an innovative ten-block model for building a high-performance team and draws on the best-on-the-topic articles from thirty-five years of Annuals volumes.